QUANTITAVE STRUCTURE-ACTIVITY RELATIONSHIP ANALYSIS (QSAR) OF ANTIMALARIAL 1,10-PHENANTHROLINE DERIVATIVES COMPOUNDS - Ruslin Hadanu; Sabirin Mastjeh; Mustofa Mustofa; Eti Nurwening Sholikhah; Mahardika Agus Wijayanti; Iqmal Tahir (Indonesian Journal of Chemistry, 2007)
Quantitative Electronic Structure-Activity Relationship (QSAR) analysis of a series of 1,10-phenanthroline derivatives as antiplasmodial compounds have been conducted using atomic net charges (q), dipole moment (μ) ELUMO, EHOMO, polarizability (α) and log P as the descriptors. The descriptors were obtained from computational chemistry method using semi-empirical PM3. Antiplasmodial activities were taken as the activity of the drugs  against  chloroquine-resistant Plasmodium falciparum FCR3 strain and are presented as the value of ln (1/IC50) where IC50 is an effective concentration inhibiting 50% of the parasite growth. The best model of QSAR model was determine by multiple linear regression method and giving equation of QSAR: ln 1/IC50  =  3.732 + (5.098) qC5 + (7.051) qC7 + (36.696) qC9 + (41.467) qC11 -(135.497) qC12 + (0.332) μ -                    (0.170) α + (0.757) log P.The equation was significant on the 95% level with statistical parameters: n=16; r=0.987; r2= 0.975; SE=0.317;  Fcalc/Ftable = 15.337 and gave the PRESS=0.707. Its means that there were only a relatively few deviations between the experimental and theoretical data of antimalarial activity.